Advances in pharmacology & therapeutics II. - Yoshida, H.; Hagihara, Y.; Ebashi, S. (Setsuro) (Pergamon., 1982)
Advances in Pharmacology and Therapeutics II, Volume 1: CNS Pharmacology Neuropeptides contains the proceedings of the Eighth International Congress of Pharmacology held in Tokyo in 1981. This book is the first of a six-volume compilation of the scientific papers of invited speakers. Separating 26 papers as chapters, this book begins with an invited lecture on opioid peptides and their receptors. Other chapters describe opioid peptides and their relevance to central nervous system mechanisms; neuropeptides and related compounds affecting learning and memory; and pharmacological approaches to t.